Italian zoos and birds: May them be a ‘missing link’ to improve public interest in birds? (Avocetta, 2022)
Zoos are well-known for conservation efforts benefiting wildlife, including some European bird species such as the Bearded Vulture Gypaetus barbatus and Waldrapp Ibis Geronticus eremiticus. In Italy there has generally been a lack of scientific interest towards zoos, and ornithology is no exception. Yet, zoo collections not only may present valuable research opportunities, but also may offer valuable insight into psychological mechanisms that make some bird species attractive to visitors while others are practically of zero exhibit value. The lack of specialized bird parks in Italy seems to suggest indirect evidence of the lack of interest in most birds by the general Italian visitor, a fact that in the long-term could have consequences for public attitudes towards bird conservation. Zoos’ experiences in species selection for attractiveness may be useful for conservation campaigns, but greater efforts toward neglected taxa should certainly be useful to increase public interest in biodiversity and ecosystem conservation with particular reference to birds.
Keywords: evolutionary psychology; conservation campaigns; conservation breeding; bird park; species attractiveness